Design approach for customers experience in services - Majid, Ahmad Zuhairi Abdul; Shaari, Hjh. Nazlina; Abdul Rahman, Hj. Khirul Aidil Azlin; Mohd Yusoff, Saiful Bahari (2011)
In this paper, we examine customers’ behavior that influenced service provider’s evaluation of experience received. The method used in this research was a collection of quantitative data. A set of questionnaire was constructed through an analysis of keywords from literature reviews employing the KJ method. In order to fulfill the objective of this research, quantitative data was gathered from a survey to see how Malaysian customers perceive the automotive service centers. Service centers were selected from different brand names or car manufacturers. Each manufacturer represented by one biggest service center that they have in Malaysia. Statistical output from this case study analyzed to form a model that can represent a new strategy for service design development. This paper also shows the evaluation of proposals and models created through interviews with service related personnel.